Melatonin Inhibits Transforming Growth Factor-β1-Induced Epithelial–Mesenchymal Transition in AML12 Hepatocytes - Jung-Yeon Kim; Jae-Hyung Park; Kiryeong Kim; Jaechan Leem; Kwan-Kyu Park (Biology, 2019)
Recent studies showed that melatonin, a well-known pineal hormone that modulates the circadian rhythm, exerts beneficial effects against liver fibrosis. However, mechanisms for its protective action against the fibrotic processes remain incompletely understood. Here, we aimed to explore the effects of the hormone on transforming growth factor-β1 (TGF-β1)-stimulated epithelial−mesenchymal transition (EMT) in AML12 hepatocytes. Pretreatment with melatonin dose-dependently reversed downregulation of an epithelial marker and upregulation of mesenchymal markers after TGF-β1 stimulation. Additionally, melatonin dose-dependently suppressed an increased phosphorylation of Smad2/3 after TGF-β1 treatment. Besides the canonical Smad signaling pathway, an increase in phosphorylation of extracellular signal-regulated kinase 1/2 and p38 was also dose-dependently attenuated by melatonin. The suppressive effect of the hormone on EMT stimulated by TGF-β1 was not affected by luzindole, an antagonist of melatonin membrane receptors, suggesting that its membrane receptors are not required for the inhibitory action of melatonin. Moreover, melatonin suppressed elevation of intracellular reactive oxygen species (ROS) levels in TGF-β1-treated cells. Finally, TGF-β1-stimulated EMT was also inhibited by the antioxidant N-acetylcysteine. Collectively, these results suggest that melatonin prevents TGF-β1-stimulated EMT through suppression of Smad and mitogen-activated protein kinase signaling cascades by deactivating ROS-dependent mechanisms in a membrane receptor-independent manner.